AGUSTUS FACTORS AFFECTING KNOWLEDGE OF PUBLIC MOTHERS ABOUT BATHING BABIES IN SIHITANG ENVIRONMENT III KOTA PADANGSIDIMPUAN - Efrida Yanti; Amvina Amvina (Institute of Computer Science (IOCS), 2022)
How to bathe a baby is a way of cleaning the baby's body with water by using a washcloth, soaking yourself in water according to the appropriate sequences. According to (WHO), it is estimated that every year 20 million postpartum mothers do not bathe their own babies for fear of falling and drowning. Given the importance of the benefits of how to bathe a baby, namely maintaining body hygiene and providing a sense of comfort for the baby. The purpose of this study was to determine the factors that influence postpartum mothers' knowledge of how to bathe babies in Sihitang Village III, Padangsidimpuan City in 2020, based on age, education, parity, and sources of information. The research time is from June 2019 to June 2020. The type of research is quantitative with a descriptive design. This sample was carried out by accidental sampling . This research was all postpartum mothers in the environment III Sihitang Village, Padangsidimpuan City in 2020 with a total of 15 respondents and this sample was taken by accidental sampling . The types of data used were primary and secondary. The results of the study were the majority aged 26-30 years were 7 respondents (46.7%), and the minority aged 31-35 years were 2 respondents (13.3%). Based on the education of the majority of primary schools as many as 8 respondents (53.3%), and university minorities as many as 1 respondent (6.7%). Based on parity, the majority of primiparas were 9 respondents (60%), and the minority of grandemultiparous mothers was 1 respondent (6.7%). Based on the work of the majority of health workers as many as 10 respondents (66.7%), and the minority of electronic media as many as 2 respondents (13.3%). It can be concluded that the knowledge of postpartum mothers about how to bathe babies in the Sihitang Village, Environment III, Padangsidimpuan City in 2020 is quite knowledgeable. Suggestions for health workers to provide clearer information both in the form of counseling and health education on how to bathe babies. Suggest for respondents to increase their knowledge, especially about how to bathe babies